HYGIENE SANITASI DEPOT AIR MINUM - Evino Sugriarta (Jurnal Sehat Mandiri, 2018)
This study aims to investigate the implementation of sanitation hygiene in drinking water depot in Padang city. The results of this study is still 45.2% drinking water depot that has the implementation of sanitation hygiene is still not good. Most factors are still not good is the behavior of employees depot in conducting drinking water treatment. Recommendation is to supervise, provide counseling, and training for owners and employees of sanitation hygiene water depots.